Influence of InGaN growth rate on the localization states and optical properties of InGaN/GaN multiple quantum wells. (September 2016) - Li, X.; Zhao, D.G.; Yang, J.; Jiang, D.S.; Liu, Z.S.; Chen, P.; Zhu, J.J.; Liu, W.; He, X.G.; Li, X.J.; Liang, F.; Zhang, L.Q.; et al.
Abstract: The localization effect is studied in blue-violet light emitting InGaN/GaN multiple quantum wells (MQWs) with varying InGaN growth rate. The temperature-dependent photoluminescence (PL) measurement shows that for higher-growth-rate samples two emission peaks appear in their PL spectra. Further analysis reveals that two different localization luminescence states (i.e., deep and shallow localization states) exist in the InGaN QWs with higher QW growth rate, and the competition of radiative recombination between the two localization states determines the relative intensity of the two emission peaks. It is also found that, as InGaN growth rate reduces, the deep localization state depth is almost unchanged while the shallow localization state weakens. When the QW growth rate reduces to a certain value, the shallow localization state disappears and only a single main peak induced by deep localization state appears in the PL spectra. Finally, it is noted that an intermediate InGaN growth rate results in a better light emission efficiency of the MQW. Highlights: The photoluminescence spectra of InGaN/GaN MQWs with varying InGaN growth rate is measured. Two classes of localization states exist in InGaN MQWs with higher QW growth rate. Only a single class of localization states exists in InGaN MQWs with lower QW growth rate. The shallow localization states weaken with reducing InGaN growth rate. The depth of deep localization states is unchanged with increasing InGaN growth rate.